Adroitly and Persuasively Preaching to the Microbial Choir<source>March of the Microbes: Sighting the Unseen</source>, by <person-group> <name name-style="western"> <surname>Ingraham</surname> <given-names>John L.</given-names> </name> </person-group> ( <year>2010</year>). <publisher-name>Harvard University Press</publisher-name>, <publisher-loc>Cambridge, MA</publisher-loc>. <fpage>326</fpage> pages. - Mark O. Martin (American Society for Microbiology, 2010)
Review of: March of the Microbes: Sighting the Unseen, by John L. Ingraham (2010) . Harvard University Press, Cambridge, MA. 326 pages.